2020
DOI: 10.1111/cup.13916
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of HMB45 and negative PRAME expression in halo nevi

Abstract: Background: Traditionally, most cutaneous nevi show a gradient of HMB45 (human melanoma black 45) and negative PRAME (preferentially expressed antigen in melanoma) immunostaining, while melanomas often show irregularly positive, diffusely positive or completely negative HMB45 expression, and PRAME immunopositivity. However, we have occasionally observed benign halo nevi with loss of HMB45 gradient, raising diagnostic consideration for melanoma. The purpose of this study was to elucidate the expression pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
(72 reference statements)
3
15
0
Order By: Relevance
“…In most cases, a "wait and see" approach is done in halo nevus cases and requires no invasive treatments, except when the underlying lesions have the possibility of malignancies. However, due to cosmetical consideration with such prominent hypopigmented patches on the facial area, we decided to perform punch biopsy and excision [2], [13].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, a "wait and see" approach is done in halo nevus cases and requires no invasive treatments, except when the underlying lesions have the possibility of malignancies. However, due to cosmetical consideration with such prominent hypopigmented patches on the facial area, we decided to perform punch biopsy and excision [2], [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent paper by Ruby at al. showed that negative PRAME immunostaining may be a reassuring finding to help differentiate halo nevus from melanoma, which would have been considered in the setting of an invasive biopsy which was avoided due to lack of concerning RCM features [12].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, rising attention is being devoted to this marker, and new studies are being conducted in an attempt to increase experiences, report results, and find safer answers [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%